(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
As the world energy market was still getting used to OPEC+’s production restrictions and the fallout from Russia’s invasion of Ukraine, geopolitical tensions in the Middle East continued to escalate, causing unease since October 7,2023. Palestinian political and military organisation Hamas attacked Israel on 7 October, reigniting years of conflict between Palestine and Israel. Israel has been violently responding to Hamas by bombing the Palestinian Gaza region for over a month now, and the growing casualty toll has kept the commodities market in a state of unease. As a result, on dramatically changing geopolitical situation in the region also illustrated that how last decade Arabian countries playing important role with relationship gigantic states. Qatar one of states that immediately reacted to this humanitarian crises. Official Doha are threatening to create a global gas shortage as part of their support for Palestine. “If the bombing of Gaza does not stop, we will cut off the gas supply to the world,” said Emir Tamim bin Hamad Al Thani.